Mass spectrometric characterization of organosulfates related to secondary organic aerosol from isoprene. (4th March 2013) - Safi Shalamzari, Mohammad; Ryabtsova, Oxana; Kahnt, Ariane; Vermeylen, Reinhilde; Hérent, Marie‐France; Quetin‐Leclercq, Joëlle; Van der Veken, Pieter; Maenhaut, Willy; Claeys, Magda
Abstract : RATIONALE: A considerable fraction of atmospheric particulate fine matter consists of organosulfates, with some of the most polar ones originating from the oxidation of isoprene. Their structural characterization provides insights into the nature of gas‐phase precursors as well as into formation pathways. METHODS: The structures of unknown polar organosulfates present in ambient particulate fine matter were characterized using liquid chromatography/(−)electrospray ionization mass spectrometry (LC/(−)ESI‐MS), including ion trap MS n and accurate mass measurements, derivatization of the carbonyl group into 2, 4‐dinitrophenylhydrazones, detailed interpretation of the MS data, and in a selected case comparison of their LC and MS behavior with that of synthesized reference compounds. RESULTS: Polar organosulfates with molecular weights (MWs) of 156, 170, 184 and 200 were attributed to/or confirmed as derivatives of glycolic acid (156), lactic acid (170), 1, 2‐dihydroxy‐3‐butanone (184), glycolic acid glycolate (200), 2‐methylglyceric acid (200), and 2, 3‐dihydroxybutanoic acid (200). In the case of the MW 184 compound an unambiguous assignment was obtained through synthesis of reference compounds. CONCLUSIONS: A more complete structural characterization of polar organosulfates that originate from isoprene secondary organic aerosol was achieved. An important atmospheric finding is the presence of an organosulfate that is related to methyl vinyl ketone, a major gas‐phase oxidation product of isoprene. In addition, minor polar organosulfates related to crotonaldehyde were identified. Copyright © 2013 John Wiley & Sons, Ltd.